2016
DOI: 10.30638/eemj.2016.057
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticide Residues in Soil and Edible Vegetable

Abstract: Intensive vegetable crops are stressed by the influence of a large number of chemicals, applied to stimulate fructification, ripening, fertilization, pathogen, pest and weed control. The purpose of this study was to highlight the impact and risk on soil and vegetable plants and products during treatments application with organochlorine pesticides, on three cultivation systems: conventional, organic and in-conversion. The objective of this study was to monitor the content of organochlorine pesticide (OCPs) resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Lettuce (Lactuca sativa L.) is one of the most consumed fresh vegetables in the world. It can be grown on soil or hydroponic conditions 31 . The common practice used to improve the yield is applying chemicals, but these are known to affect the environment 32 .…”
mentioning
confidence: 99%
“…Lettuce (Lactuca sativa L.) is one of the most consumed fresh vegetables in the world. It can be grown on soil or hydroponic conditions 31 . The common practice used to improve the yield is applying chemicals, but these are known to affect the environment 32 .…”
mentioning
confidence: 99%
“…found that an infinite amount of nitrate in surface water is related either to the increased algal growth in these sites [SLIM et al, 2005. BONCIU et al, 2018BONEA et al, 2018;GROZEA et al, 2017, STOLERU et al, 2016 , or to the joint "denitrification" phenomenon that converts NO3nitrate to N2 through the presence of nitrate organic material. Indeed, the dissolved phosphorus is not absorbed by living microorganisms and its content remains more or less unchanged in low oxygen environments.…”
Section: Resultsmentioning
confidence: 99%
“…was found that during densification, the densities of rice husk increased from 0.196g/m 3 (196 kg/m 3 ) to between 513 kg/m 3 -765 kg/m 3 with GS as binder; 472-762 kg/m 3 with AAW as binder [BONEA et al, 2017, PENTEA et al, 2016, STOLERU et al, 2012 ; and 542 -786 kg/m 3 with AAP as binder. It was also observed that briquettes of higher densities were obtained at higher die pressure for all the binders [BONCIU et al, 2018;BONEA et al, 2018;GROZEA et al, 2017, STOLERU et al, 2016 .…”
Section: Itmentioning
confidence: 97%
“…Physical characterization of rice husk. Particle size distribution, bulk density, and particle density analysis were carried out using ASAE standards and gas pycnometry respectively [ASABE BONCIU et al, 2018;BONEA et al, 2018;GROZEA et al, 2017, STOLERU et al, 2016 .…”
Section: Equipmentmentioning
confidence: 99%
See 1 more Smart Citation